DNA Damage Response and Repair Gene Alterations Increase Tumor Mutational Burden and Promote Poor Prognosis of Advanced Lung Cancer - Dai, Jiawei; Jiang, Minlin; He, Kan; Wang, Hao; Chen, Peixin; Guo, Haoyue; Zhao, Wencheng; Lu, Hui; He, Yayi; Zhou, Caicun (Frontiers in Oncology, 2021)
DNA damage response and repair (DDR) gene alterations increase tumor infiltrating lymphocytes, genomic instability, and tumor mutational burden (TMB). Whether DDR-related alterations relate to therapeutic response and prognosis in lung cancer lacking oncogenic drivers remains unknown. Pre-therapeutic cancer samples of 122 patients [86 non-small cell lung cancer and 36 small cell lung cancer (SCLC)] harboring no EGFR/ALK alterations were collected. Through whole-exome sequencing, we outlined DDR mutational landscape and determined relationships between DDR gene alterations and TMB or intratumoral heterogeneity. Then, we evaluated the impacts of DDR gene alterations on therapeutic response and prognosis and established a DDR-based model for prognosis prediction. In addition, we investigated somatic interactions of DDR-genes and immunomodulatory genes, immune expression patterns, immune microenvironment and immune infiltration characteristics between DDR-deficient and DDR-proficient samples. Samples from cBioportal datasets were utilized for verification. We found that deleterious DDR gene alterations were closely associated with higher TMB than proficient-types (P<0.001). DDR mechanisms attach great importance to the determination of patients’ prognosis after chemotherapy, and alterations of base excision repair pathway in adenocarcinoma, nucleotide excision repair in squamous carcinoma, homologous recombination pathway in SCLC tend to associate with worse progression-free survival to first-line chemotherapy (all P<0.05). A predictive nomogram model was constructed incorporating DDR-related alterations, clinical stage, metastasis, and smoking status, with the area under curve values of 0.690-0.840 for 1- and 2-year receiver operating characteristic curves in training and testing cohorts. Furthermore, DDR-altered tumors contained enhanced frequencies of alterations in various genes of HLA class I pathway including TAP1 and TAP2 than DDR-proficient samples. DDR-deficient types had lower expressions of STING1 (P=0.01), CD28 (P=0.020), HLA-DRB6 (P=0.014) in adenocarcinoma, lower TNFRSF4 (P=0.017) and TGFB1 expressions (P=0.033) in squamous carcinoma, and higher CD40 (P=0.012) and TNFRSF14 expressions (P=0.022) in SCLC. DDR alteration enhanced activated mast cells in adenocarcinoma (P=0.044) and M2 macrophage in squamous carcinoma (P=0.004) than DDR-proficient types. Collectively, DDR gene alterations in lung cancer without oncogenic drivers are positively associated with high TMB. Specific DDR gene alterations tend to associate with worse progression-free survival to initial chemotherapy.